Perceived spouse's affectionate and antagonistic behaviours and marital satisfaction - Jelić, Margareta (Array, 2014)
The aim of the study was to examine how perceived spouse’s affectionate and antagonistic behaviors contribute to one’s marital satisfaction. Firstly, we explored whether perception of partner’s affectionate and antagonistic behaviours vary with gender, age, length of marriage and family structure. Secondly, we examined the relation between perceived partner’s behaviour and marital satisfaction, while controlling for contextual variables. Questionnaire assessing love, marital satisfaction, perceived partners’ affectionate and antagonistic behaviours and demographic data was administered to a heterogeneous sample of 302 married couples from Croatia with the average marriage length of 18 years and age span of 20–82 years. Results indicate that perceived spouse’s affectionate and antagonistic behaviours both contribute to marital satisfaction with the impact of antagonistic behaviours being buffered when it appears in affectionate relationship. These effects are not moderated by age, gender, marriage duration or family structure. Finally, the perception of partner’s affectionate and antagonistic behaviours had significant incremental power over feelings of love and other contextual variables when predicting marital satisfaction.